ADVOCACY CAMPAIGNS OF GREENPEACE IN ADDRESSING AIR POLLUTION PROBLEMS IN AFRICA - Alfredha Shinta Putri (Intermestic: Journal of International Studies, 2026)
Air pollution is a major environmental and public health problem in Africa, contributing to hundreds of thousands of premature deaths annually. Countries such as South Africa, Nigeria, and Egypt face high levels of pollutants, including nitrogen dioxide (NO₂), sulfur dioxide (SO₂), and particulate matter (PM2.5), primarily caused by fossil fuel combustion, industrial activities, transportation, and household fuel use. This study examines Greenpeace’s advocacy campaigns in addressing air pollution challenges across the continent. As an independent international non-governmental organization, Greenpeace promotes renewable energy transition, stronger environmental regulations, and improved public awareness. Its strategies include digital campaigns, online petitions, social media mobilization, public framing techniques, and direct engagement with political leaders, particularly during election periods. Through these approaches, Greenpeace seeks to influence policy reform and pressure governments to adopt cleaner energy systems. The study concludes that effective advocacy, combined with regulatory strengthening and renewable energy adoption, is essential to reduce environmental injustice, protect public health, and support sustainable development in Africa.